Correlational Relationship between Pediculosis and Hemoglobin Levels in Female Students of the Salafiyah Addamanhuri Islamic Boarding School - Anggraini, Dwi Aprilia; Fahmi, Norma Farizah; Mawli, Rizka Efi; Fauziyah, Shifa; Irawan, Heri (Journal of Parasite Science, 2026)
Pediculus humanus capitis is one of the parasitic species, namely the human blood-sucking fleas. Hair lice can cause itching, scalp irritation and pediculosis. People with pediculosis can cause a lack of hemoglobin. The beginning of the transmission of pediculosis in students is the habit of borrowing personal items such as head accessories so that students easily experience pediculosis. The aim of this research is to establish the connection between pediculosis infection and hemoglobin levels in female students of the Salafiyah Addamanhuri Islamic Boarding School. This research used qualitative descriptive with  a cross sectional design of the sample used was 75 students using purposive sampling techniques. Research location was at the Salafiyah Addamanhuri Islamic Boarding School and the Microbiology Laboratory of the DIII Health Analyst Health Analyst of Universitas NHM. The examination method is the POCT method and data analysis tool is SPSS with a chi-square statistical test. The findings from this research unveil that 50 students (66.7%)  were positive for pediculosis  and 25 students (33.3%) were not infected with pediculosis. Then students with hemoglobin below normal as much as 64% and normal hemoglobin levels as much as 36%. The analysis of the relationship between pediculosis and hemoglobin levels was carried out based on a chi-square test with a significance level of P=<0.05, the analysis revealed a P=<0.004. Indicating a significant relationship between pediculosis and hemoglobin levels in female students of the Salafiyah Addamanhuri Islamic Boarding School.